John Rawls' Theory of Justice in the Perspective of Shareholder Rights Protection (Lembaga Pengembangan Kinerja Dosen, 2025)
John Rawls' Theory of Justice offers a robust conceptual framework for developing fair legal policies, particularly in the context of post-merger and acquisition corporate integration. This article explores Rawls' justice as fairness, focusing on the application of the difference principle to ensure proportional benefit distribution and the equal liberty principle to protect shareholder rights. In corporate integration processes, Rawls' principles emphasize the importance of fair treatment for all stakeholders, especially vulnerable groups such as minority shareholders, through transparency and accountability in decision-making. The article also contextualizes Rawls' theory with Mochtar Kusumaatmadja's developmental legal approach, which views law as a tool to balance economic dynamics and social justice. Using a doctrinal method, this study demonstrates that Rawls' principles provide a philosophical foundation for creating responsive and inclusive corporate regulations. These regulations not only promote economic efficiency but also protect the rights of vulnerable groups, making them relevant to addressing modern legal challenges.